Nursing students' experiences of moral uncertainty in the context of global health practicums. Issue 3 (14th December 2021) - Greig, Madeleine; Pesut, Barbara; Marck, Patricia; Burgess, Michael
Abstract: More students than ever are electing to take part in international practicums from health‐related disciplines. With the goal of better understanding the moral experiences and ethical implications of global health practicums (GHPs), the purpose of this Interpretive Descriptive study was to examine the moral uncertainty of nursing students from one university in Canada. Seventeen nurses who had participated in a GHP in their undergraduate nursing program participated in semi‐structured interviews. Data were analyzed inductively using constant comparative data analysis techniques, and a thematic account of participants' experiences was developed. Findings suggest that nursing students experienced considerable amounts of moral uncertainty during their GHP. Most often, participants' experiences of uncertainty stemmed from a misalignment between their expectations and reality, including encountering different approaches to healthcare, being situated in new cultural and clinical care environments, and grappling with how best to stay within one's scope of student professional practice. Participants inconsistently reflected on these experiences, which may present a missed opportunity for professional growth through the development of a heightened social consciousness. Educators can facilitate this process by implementing robust predeparture training for GHPs, clarifying program objectives, and providing clinical debriefing.